2018
DOI: 10.1016/j.jmmm.2017.09.058
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and magnetotransport properties of Bi2Se3 thin films doped by Eu

Abstract: Structural, magnetic and magnetotransport properties of (Bi 1−x Eu x ) 2 Se 3 thin films have been studied experimentally as a function of Eu content. The films were synthesized by MBE. It is demonstrated that Eu distribution is not uniform, it enter quint-layers forming inside them plain (pancake-like) areas containing Eu atoms, which sizes and concentration increase with the growth of Eu content. Positive magnetoresistance related to the weak antilocalization was observed up to 15K. The antilocalization was … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…It is not necessarily that Sr atoms are randomly distributed in the lattice. We can't exclude formation of metal-rich nanoclusters [29,41], flat inclusions [42], segregation [43], or even well arranged blocks [44]. However, in XRD similar imperfections are usually manifested just as a broadening of the reflections, while detection of the specific Sr-enriched structures by means of TEM is rather challenging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not necessarily that Sr atoms are randomly distributed in the lattice. We can't exclude formation of metal-rich nanoclusters [29,41], flat inclusions [42], segregation [43], or even well arranged blocks [44]. However, in XRD similar imperfections are usually manifested just as a broadening of the reflections, while detection of the specific Sr-enriched structures by means of TEM is rather challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Thin films with different Sr content were obtained by varying the evaporation temperature of the Sr effusion cell. Sr concentration x in the grown films was increased from 0.003 to 0.352 when heating Sr cell from 260 to 380 • C. When growing Bi 2 Se 3 films from elemental Bi and Se sources [18][19][20][21]23] it is inevitable to employ a two-step deposition method due to a weak interaction of Bi and Se ad-atoms with the substrate, with the first step temperature being below 150 • C. Beam flux composition, generated from effusion cell loaded with binary Bi 2 Se 3 compound [22,28,29], consists of Bi-Se molecular species [24], and thin film condensation occurs at the elevated temperatures. So, time consuming low temperature stage becomes unnecessary.…”
Section: Growth and Structural Characterization Techniques Growth Tec...mentioning
confidence: 99%
“…However, despite having achieved substitutional doping of high-quality Bi 2 Te 3 films with Gd, Dy, and Ho, [80][81][82] all films remained essentially paramagnetic with some hints of antiferromagnetic behavior. [80][81][82][83][84] Although Eu-doped Bi 2 Se 3 has demonstrated ferromagnetism with over 10% Eu concentration, the doing profile in this system is not uniform, [85] which is an issue for transport measurements. Nevertheless, for Dy doping, it is already shown that low fields of 0.65 T can result in induced moments on the order of ≈1/3 of the full Dy 3 + moment in Dy:Bi 2 Te 3 .…”
Section: Dopingmentioning
confidence: 99%
“…The Eu-doped Bi 2 Se 3 thin films were synthesized by the molecular-beam epitaxy technique using evaporation cells with binary Bi 2 Se 3 source as well as cells with elemental Bi, Se, and Eu. More detailed description of the growth process and structural characterization of studied films can be found in [16,17]. For simplicity, we can consider our films as ternary (Bi 1−x Eu x ) 2 Se 3 compounds and use x as a measure of Eu content.…”
Section: Samples and Experimental Setupmentioning
confidence: 99%